Influence of the strain of rats on the induction of hexachlorobenzene induced porphyria - Wainstok de Calmanovici, R. (1989)
1. 1. The present work undertakes a comparative study on the hexachlorobenzene (HCB) porphyria induction in female rats of Wistar and CHBBTHOM strains. The purpose was to characterize the CHBBTHOM strain with respect to the haem metabolic pathway, its regulatory mechanisms and its response to foreign drugs. 2. 2. After 7 weeks of treatment it was observed that the hepatic porphyrins increased 140 times, ALA-synthase 4 times and PCL was 73% inhibited in the Wistar strain. 3. 3. On the other hand the animals of CHBBTHOM strain showed lesser alteration on these parameters; hepatic porphyrins increased only 3-fold, ALA-synthase 1.7-fold and PCL was only 22% inhibited. 4. 4. Total iron liver content was nearly equal in both strains of rats. 5. 5. The results obtained would indicate that the lower susceptibility of the CHBBTHOM strain to acquire porphyria does not seem to be due to either: (1) congenital alterations of any parameters of the haem metabolic pathway, since the behaviour of normal animals from both strains was similar; or (2) a lower hepatic iron content in such animals. 6. 6. These findings would suggest that the differential response to HCB to this strain would be looked for in another metabolic pathway, such as that involved in the metabolization process of the toxic. © 1989.